Transition of transnational social workers: a critical realist perspective on the need for a response from the profession - Shajimon Peter; Allen Bartley; Liz Beddoe; Lynne Soon-Chean Park; Liyun Wendy Choo (Kōtuitui, 2023)
ABSTRACTThis article examines the absence of a profession-wide response for facilitating the transition of transnational social workers (TSWs) into the host country. TSWs work with various racial, ethnic, and cultural groups and often in unfamiliar socio-political, policy and practice contexts. A qualitative study was undertaken in New Zealand, which involved six focus groups, three with managers of TSWs and three with TSWs themselves and a face-to-face semi-structured interview with a manager who was also a TSW. Coding and analysis of data were informed by critical realism (CR). We found that TSWs’ transitions are framed within an employer-employee relationship in the absence of a profession-wide response and TSWs encounter structural barriers in their transition. A suggestion has been made that the profession’s leadership acknowledge responsibility that attends to the transitional space and an emotional concern about the wellbeing of TSWs. The transnational nature of the profession demands greater accountability regarding inclusion, sustainability, safety and discrimination. It can positively impact on the overall wellbeing of TSWs and the client groups they serve.